Comparative Evaluation of Salivary Ferritin Levels as a Predictor Inflammatory Biomarker Before and After Non Surgical Periodontal Therapy- An Interventional Study - Saurabh Tembhurne; Sachin K. Malagi; Dennis V. Abraham; Kshitibhushan S. Pandaw; Arundhuti Mahato; Priyal Agrawal (Journal of Pharmacy and Bioallied Sciences)
Background: Ferritin plays a crucial role in the host immune response, with elevated serum ferritin levels established in various chronic inflammation-related diseases, including periodontitis. This study aimed to evaluate the efficacy of nonsurgical periodontal treatment on salivary ferritin levels in periodontally healthy and chronic periodontitis patients. Materials and Methods: Fifty patients were selected and divided into two groups: a control group of healthy individuals and an experimental group of chronic periodontitis patients. Salivary samples were collected using the drooling method to assess ferritin levels. The experimental group underwent nonsurgical periodontal therapy, with clinical parameters [plaque index (PI), gingival index (GI), oral hygiene index-simplified (OHIS), bleeding point index (BPI), probing pocket depth (PPD), and clinical attachment level (CAL)] recorded before and one month after therapy. Salivary samples were analyzed using CLIA, and statistical analysis was performed. Results: The control group showed significantly lower ferritin levels compared to the periodontitis group. Post-therapy, the periodontitis group exhibited significant improvements in both clinical parameters and ferritin levels. Conclusion: Salivary ferritin levels effectively predict periodontal disease and the impact of periodontal therapy, demonstrating its potential as a valuable biomarker for diagnosing and monitoring periodontal health.